Konsep Masyarakat Madani Dalam Demokrasi Pancasila - Muhammad Pengkuh Wedhono Jati (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Western democracy that was born by the French Revolution did not bring true people's independence, but gave rise to the power of capitalism, therefore political democracy alone is not enough to achieve true democracy, namely people's sovereignty. There must also be economic sovereignty, which uses the basis, that all income which recognizes the livelihood of the people must be under the responsibility of the people as well. The basis of identity awareness is the embryo of the birth of civilization, whereas if we look at the basis of identity awareness of Western nations (US and Western Europe) the differences are very clear, Western countries: individualist, humanist, secular, while Indonesian society: individual-social, humanist-religious, religious. So it is natural that at the level of implementation, democracy in Indonesia is different from democracy that develops in the West, because the basis for awareness of the identity of the two is very different. Nurcholish Madjid is an icon of Islamic scholars who is considered the most controversial and the most contributive. The main ideas are among the three major themes; Islam, Indonesianness and Modernity. Nurcholish Madjid campaigned for civil society, a concept of society that started from the time of the prophet Muhammad SAW with the principles of egalitarianism, pluralism, equality of human rights and protecting minorities.